2017
DOI: 10.1016/j.metabol.2017.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids modulate human brown adipose tissue thermogenesis in vivo

Abstract: IntroductionBrown adipose tissue (BAT) is a thermogenic organ with substantial metabolic capacity and has important roles in the maintenance of body weight and metabolism. Regulation of BAT is primarily mediated through the β-adrenoceptor (β-AR) pathway. The in vivo endocrine regulation of this pathway in humans is unknown. The objective of our study was to assess the in vivo BAT temperature responses to acute glucocorticoid administration.MethodsWe studied 8 healthy male volunteers, not pre-selected for BAT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 41 publications
2
38
0
3
Order By: Relevance
“…Administering healthy male subjects with three doses of prednisolone (the first dose was administered 24 h before visiting the research facility) had no effect on basal BAT activity; however, PET and infrared thermography of skin temperature in the supraclavicular region revealed that cold-induced glucose uptake in BAT and skin temperature were enhanced by prednisolone (Ramage et al, 2016). An independent study using infrared thermography demonstrated that infusing healthy male subjects with hydrocortisone for 24 h had no effect at room temperature; however, a cold-induced increase in skin temperature of the supraclavicular region was enhanced (Scotney et al, 2017). Results obtained in cell culture are in line with these observations.…”
Section: Glucocorticoidsmentioning
confidence: 58%
“…Administering healthy male subjects with three doses of prednisolone (the first dose was administered 24 h before visiting the research facility) had no effect on basal BAT activity; however, PET and infrared thermography of skin temperature in the supraclavicular region revealed that cold-induced glucose uptake in BAT and skin temperature were enhanced by prednisolone (Ramage et al, 2016). An independent study using infrared thermography demonstrated that infusing healthy male subjects with hydrocortisone for 24 h had no effect at room temperature; however, a cold-induced increase in skin temperature of the supraclavicular region was enhanced (Scotney et al, 2017). Results obtained in cell culture are in line with these observations.…”
Section: Glucocorticoidsmentioning
confidence: 58%
“…The first study to use IRT to estimate SST was performed in 2011 . Ten studies were then published between 2011 and 2016 , six in 2017 , six in 2018 , and one until April 2019 .…”
Section: Resultsmentioning
confidence: 99%
“…The first study to use IRT to estimate SST was performed in 2011 (24). Ten studies were then published between 2011 and 2016 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34), six in 2017 (35)(36)(37)(38)(39)(40), six in 2018 (16,(41)(42)(43)(44), and one until April 2019 (45).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations